THE SEXUAL DIVISION OF LABOUR IN THE ORIGINS OF MALE DOMINATION: A MARXIST PERSPECTIVE (Journal of Philosophy Culture and Political Science, 2021)
Abstract: Of all the themes that Friedrich Engels addressed 130 years ago in “The Origin of the Family, Private Property and the State”, the question of the oppression of women is one that remains particularly salient today. Serious feminists have always considered that they should base their struggle on a clear understanding of the causes and mechanisms of what they were opposing. However, since Engels’s book was written, our knowledge of primitive societies and prehistory has advanced by leaps and bounds, and has rendered many previously held positions obsolete. This article is an expression of the author’s original view on the problem of the source of the phenomenon of sexual division of labor. The aim of this essay is to suggest a framework for the updating of Marxist arguments on the subject in the light of the findings that have accumulated since then. This article summarises the ideas put forward in my book « Le communisme primitif n’est plus ce qu’il était » (2012). Key-words: Marxism, social classes, social communities, social groups, gender philosophy, feminism